Can the State Administrative Court Shield Citizens from Government 'Tort'? A Path to Justice in Dispute Resolution - Widianta, RM Ivansyah Gusti; Akbarsyah, Iqbal Salamuddin (Universitas Negeri Semarang, 2024)
In democratic governance, protecting citizens from wrongful acts by the government is crucial to maintaining public trust and ensuring justice. In Indonesia, the State Administrative Court (PTUN) serves as the primary forum for resolving disputes between individuals or legal entities and government authorities. However, when these disputes involve acts of